Faktor Yang Berhubungan Dengan Perilaku Ibu Dalam Pemberian MP-ASI Pada Bayi Usia 6-12 Bulan - Nurmadiyah, Nurmadiyah; permanasari, ika; Efliani, Destria (REAL in Nursing Journal, 2024)
Background: Complementary feeding is the transition from milk intake to semi-solid food. Complementary feeding must be introduced at the right time, be adequate, safe, and well-fed as this stage significantly impacts the health and optimal growth of the baby. Factors related to complementary feeding include family support, education, cultural, and technological factors. The aim of this research was to identify factors associated with maternal behaviour in providing complementary foods to babies aged 6–12 months in Batu Ampar Village. The design of this research was a cross-sectional study conducted in September 2023. The population and sample in this study consisted of all babies aged 6–12 months in Batu Ampar Village, totalling 47 individuals. Data were obtained from the questionnaire sheet. The data analysis used in this study was cross-sectional. The research results showed that out of 47 respondents, 21 (44.7%) had senior high school education, 29 (61.7%) reported good family support, and 29 (61.7%) indicated having a good cultural background. Additionally, 29 respondents (61.7%) used technology to provide supplementary breast milk to their babies. The results of the analysis indicate a relationship between education (p-value = 0.02), culture (p-value = 0.04), and family support (p-value = 0.018) and the behaviour of providing complementary feeding. There is no significant relationship between technology and the behaviour of providing complementary feeding (p-value = 0.102). It is recommended that health workers and families provide support and motivation to encourage caregivers to practice complementary.